Analysing Service-Level Solvency of Local Governments from Accounting Perspective: A Study of Local Governments in the Province of Yogyakarta Special Territory, Indonesia - Ritonga, Irwan Taufiq (The International Consortium on Governmental Financial Management St Michaels, Maryland United States of Americ, 2014)
This study aims to develop measures of service-level solvency of local government from an accounting perspective and to implement the measures to analyze service-level solvency of local governments in the Province of Yogyakarta Special Territory. The metrics are the first instruments developed in Indonesia to measure service-level solvency of local governments using accounting information. The metrics consist of total assets per capita, total equities per capita, total fixed assets per capita, total expenditures per capita, total public expenditures per capita, and total capital expenditure per capita. The metrics can be used as indicators to assess how sound a local government achieves its objectives. The analysis of service-level solvency of local governments during the period of2010-2012 was done by using time-series and cross-sectional analysis. Results of analysis show that all local governments showed improvement trends. Kabupaten Kulon Progo was the best local government compared with other regency local governments; Kabupaten Gunungkidul demonstrated an accelerated trend compared with other regency local governments; and Kabupaten Sleman and Kabupaten Bantul showed decreasing trends compared with its compatriot.